MEMANFAATKAN FEAR OF MISSING OUT (FOMO) DI ERA DIGITAL: PERAN PEMASARAN MEDIA SOSIAL DALAM MENGUBAH KEPUTUSAN PEMBELIAN KONSUMEN - Ulfa, Vida Maria (Journal of Innovation Research and Knowledge, 2024)
The Fear of Missing Out (FOMO) phenomenon has greatly influenced consumer purchasing decisions in the connected digital era. Using a quantitative method with a sample of 100 people who actively use social media, this study examines how Fear of Missing Out and social media marketing affect consumer purchase intentions. Through multiple linear regression analysis, it was found that both have a positive and significant impact on consumer purchasing decisions, indicating that the higher the level of Fear of Missing Out, the more intense social media marketing. The results show that Fear of Missing Out can effectively stimulate consumer engagement and that businesses should use marketing strategies that emphasize urgency and exclusivity to increase consumer engagement